Rilpivirine as a Treatment for HIV-infected Antiretroviral-naïve Adolescents: Week 48 Safety, Efficacy, Virology and Pharmacokinetics. Issue 11 (November 2016) - Lombaard, Johan; Bunupuradah, Torsak; Flynn, Patricia M.; Ramapuram, John; Ssali, Francis; Crauwels, Herta; Hoogstoel, Annemie; Van Eygen, Veerle; Stevens, Marita
Abstract : Background: Rilpivirine 25 mg qd yields similar exposure in adolescents and adults (Pediatric study in Adolescents Investigating a New NNRTI TMC278 [PAINT] Cohort 1, Part 1). We report rilpivirine safety, efficacy, virology and pharmacokinetics in adolescents during 48 weeks of treatment (Cohort 1, Part 2). Methods: PAINT (NCT00799864) is a phase II, ongoing, open-label, single-arm trial of rilpivirine plus 2 investigator-selected nucleoside/nucleotide reverse-transcriptase inhibitors. Cohort 1 of PAINT includes treatment-naïve HIV-1-infected adolescents (≥12 to <18 years). Following approval in adults and after Part 1a in Cohort 1, enrollment was restricted to screening viral load (VL) ⩽100, 000 copies/mL. Results: Overall, 20 (56%) of 36 patients were women, 18 (50%) were aged ≥12 to <15 years, 32 (89%) were Black or African American, mostly from South Africa or Uganda, and 28 (78%) had baseline VL ⩽100, 000 copies/mL. At week 48, adverse events considered possibly related to treatment occurred in 13 (36%) patients, mostly (excluding investigations) somnolence (n = 5, 14%) and nausea (n = 2, 6%). Most adverse events were grade 1 or 2, and 7 (19%) patients had grade 3 or 4 adverse events. Week 48 virologic response (VL <50 copies/mL, time-to-loss-of-virologic-response) was achieved in 26 of the 36 (72%) patients: 22 of the 28 (79%) with baseline VL ⩽100, 000 copies/mL and 4 of the 8 (50%) with baseline VL >100, 000 copies/mL. Median (range) CD4 + count increased by 184 (−135 to 740) cells/mm 3 at week 48. Eight patients experienced virologic failure, including 5 who developed rilpivirine resistance-associated mutations, mostly E138K, K101E and M230L. Mean (standard deviation) rilpivirine area-under-the-concentration-time curve from 0 to 24 hours (AUC24h and C0h ) were 2391 (991) ng·h/mL and 83.5 (38.7) ng/mL, respectively. Conclusions: Rilpivirine safety, virologic and pharmacokinetic profiles were similar in treatment-naïve HIV-1-infected adolescents and adults, supporting use of rilpivirine 25 mg qd, plus other antiretrovirals, in treatment-naïve adolescents with VL ⩽100, 000 copies/mL at treatment initiation.